Role of the Mitochondrion in Programmed Necrosis - Baines, Christopher (Frontiers in Physiology, 2010)
In contrast to the “programmed” nature of apoptosis and autophagy, necrotic cell death has always been believed to be a random, uncontrolled process that leads to the “accidental” death of the cell. This dogma, however, is being challenged and the concept of necrosis also being “programmed” is gaining ground. In particular, mitochondria appear to play a pivotal role in the mediation of programmed necrosis. The purpose of this review, therefore, is to appraise the current concepts regarding the signaling mechanisms of programmed necrosis, with specific attention to the contribution of mitochondria to this process.